The impact of CO2 laser on the bond strength of translucent zirconia and traditional zirconia with the resin cement: In vitro study - Saker Rima Jawdat; Zleik Bashar Moukhles (Balkan Stomatological Society, 2024)
Background/Aim: The aim of this study is to compare the impact of CO 2 laser on traditional zirconia and translucent zirconia in terms of the bonding strength to resin cement. Material and Methods: In this in-vitro study 20 zirconia disks (10 mm diameter and 2 mm thickness) were assigned to two groups (n = 10). Group 1: 10 discs of traditional zirconia, Group 2: 10 discs of translucent zirconia, CO 2 lasers were used for pretreatment of zirconia surface, respectively. Dentinal disks were cemented on zirconia disk using dual-curing resin cement. Shear bond strength tests were performed at a crosshead speed of 1 mm/min after 24 h distilled water storage. Data was analyzed by T Student's test. Results: The means and standard deviations of shear bond strength values in Group 1, and Group 2 were 1.15, 0.38, 1.99 , 0.65 MPa respectively. Data showed that application of CO 2 laser resulted in a significant higher shear bond strength of resin cement to translucent zirconia ceramics (p < 0.05). Conclusions: Application of CO 2 laser treatment (3W) increases the bond strength to the resin cement of translucent zirconia compared to traditional zirconia.